Association between the miRNA‐149 rs2292832 T>C polymorphism and Kawasaki disease susceptibility in a southern Chinese population. Issue 4 (29th November 2019) - Li, Jiawen; Wang, Jinxin; Su, Xiaoping; Jiang, Zhiyong; Rong, Xing; Gu, Xueping; Jia, Chang; Zeng, Lanlan; Zheng, Hao; Gu, Xiaoqiong; Chu, Maoping
Abstract: Background: Kawasaki disease (KD), which is characterized by vasculitis, is prone to occur in patients under 5 years of age, has an ambiguous etiology, and displays coronary artery lesions as the chief complication. Previous studies have linked miRNA‐149 to cancers, and rs2292832 T>C is related to allergic diseases and inflammatory bowel disease, which both show immune system disorders and coronary artery disease. Therefore, we performed a study concentrating on the association between the miRNA‐149 rs2292832 T>C polymorphism and KD susceptibility. Methods: The subjects enrolled were 532 children with KD and 623 controls. We used TaqMan real‐time PCR to obtain the genotypes of the rs2292832 T>C polymorphism. Results: Ultimately, no significant association was found between the miRNA‐149 rs2292832 T>C polymorphism and KD susceptibility, even in stratification analysis. Conclusion: Our results indicated that in southern Chinese patients, the miRNA‐149 rs2292832 T>C polymorphism did not affect KD susceptibility, which needs to be further confirmed.